KONSEP PENDIDIKAN MENTAL ANAK USIA DINI (Study Pemikiran Abdullah Nashih Ulwan dalam Kitab Tarbiyah Al-Aulad Fi Al-Islam) - Sirri Afifah; Fanny Fauzy Hanifunni’am (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The aims of this study are (1) to determine the concept of mental education according to Abdullah Nashih Ulwan in the book Tarbiyah Aulad Fii Islam; (2) to determine the socio-emotional development of early childhood; and (3) to determine the mental relevance of early childhood social development. This study uses an approach, the method used is literature study, with data collection techniques with book analysis, documentation. What will then be discovered and understood is the concept of mental education in early childhood according to Abdullah Nashih Ulwan in the book Tarbiyah Al Aulad Fii Al Islam. The results of this study, the concept of Early Childhood Mental Education according to Abdullah Nashih Ulwan are 1) Efforts or processes that can be carried out by parents and educators by freeing children from inferiority, cowardice, lack of feeling, jealousy, and anger. By educating children since they are able to think to be brave, honest, strong, feel perfect, enjoy doing good to others, able to control emotions, and have all the virtues of soul and character, with the aim of shaping the child's personality, perfecting it, and balancing it. ) Someone with high emotional intelligence tends to be a socially competent person. So it can be seen that emotional development has a major influence on children's social development 3) If Abdullah Nashih Ulwan's theory in the concept of children's education is applied and used today, the social emotional development of children will develop according to the stages. In addition, the relevance between the concept of mental education according to Abdulloh Nashih Ulwan and the social emotional development of children for the achievement of these developments depends on the factors that influence the development of children.